Musik Pesantren Perspektif Etnografis - Muhammad Yaser Arafat (Religi: Jurnal Studi Agama-agama, 2021)
This study tries to examine in more detail the relation between pesantren and music. This is because many people think that Islamic boarding schools have absolutely no contact with music, just because they are taught religious sciences. For example, if there is, it will refer to Islamic music such as gambus, hadrah, or marawis. Even though it is only a small part of the pesantren's music. Even though they are already familiar with Islamic music, it is not uncommon for students to also understand and memorize rock, pop, or metal music. The data collection in this study used literature study, field observations, and interviews. The results of this study indicate that students can be in touch with music without being limited by genre. Moreover, their understanding of the religion they share does not prohibit music. Music is considered haram if it brings harm. The students can freely choose the type of music, such as rock, metal, Islamic, or even dangdut as long as it doesn't make them forget from practicing religious teachings. Therefore, the emergence of the band WALI, which was founded by santri with the genre of pop songs, is not forbidden, even now it is still coloring the world of Indonesian music. On the other hand, it is not uncommon for kyai who role models for the students are to play musical instruments and sing, such as Kyai Muhajir Khozin, Kyai Faizi, and Gus Muwafiq.